Simple and low-temperature polyaniline-based flexible ammonia sensor: a step towards laboratory synthesis to economical device design1. Issue 36 (28th September 2015) - Bandgar, D. K.; Navale, S. T.; Nalage, S. R.; Mane, R. S.; Stadler, F. J.; Aswal, D. K.; Gupta, S. K.; Patil, V. B.
<x xml:space="preserve">Abstract</x> The flexible PAni ammonia sensor not only exhibits high sensitivity, good selectivity and a fast response but also has flexibility, cheap with wearable characteristics.